2021
DOI: 10.1088/1755-1315/890/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different combination of culture medium on growth and nutrition content of black soldier fly larvae (Hermetia illuens)

Abstract: Fish feed is the most essential necessity and the biggest contributor on production cost of fish cultivation. As much as 50-70% production cost is for fish feed. It can be deducted by made alternative fish feed. Black soldier fly larvae is an alternative fish feed with high protein content and most importantly it is cheap. The aim of this research was to evaluate the growth and nutrition content of black soldier fly larvae which cultivated in different medium. Medium used in this study was combination of cocon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In this investigation, RB emerged as a potentially effective dry substrate; however, numerous studies have highlighted its limitations. Previous examination of the proportion of RB mixed with coconut pulp residue revealed that BSFL did not thrive when the mixture contained over 50% (w/w) RB due to the resulting high substrate temperatures ( Muchdar et al, 2021 ). Similarly, and consistent with this study, RB could sustain BSF larval growth and rapid development when used at less than 25% (w/w) in the substrate due to its elevated protein content.…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation, RB emerged as a potentially effective dry substrate; however, numerous studies have highlighted its limitations. Previous examination of the proportion of RB mixed with coconut pulp residue revealed that BSFL did not thrive when the mixture contained over 50% (w/w) RB due to the resulting high substrate temperatures ( Muchdar et al, 2021 ). Similarly, and consistent with this study, RB could sustain BSF larval growth and rapid development when used at less than 25% (w/w) in the substrate due to its elevated protein content.…”
Section: Discussionmentioning
confidence: 99%
“…Sago and cassava dregs as well as rice straw were transformed into powders by grinding with a hammer mill and passing through an 80-mesh sieve [24]. Before grinding, all the materials were subjected to sun-drying for three days [25]. CMC, guar gum, carrageenan, and pea fiber were in the form of powder and no further treatments were applied.…”
Section: Methodsmentioning
confidence: 99%
“…The principle of water content analysis is the distillation method, which is based on the direct measurement of the amount of water removed from the sample by evaporation (Deman et al 2018). Water content is based on the difference by weight sample that determines the actual moisture before and after drying (Muchdar et al 2021). Therefore, water in materials can be used as an index of stability during storage and a determinant of organoleptic.…”
Section: Analysis Of Water Contentmentioning
confidence: 99%